Recent temporal trends in cesarean section rates in Brazil according to the Robson classification system - Rômulo Cesar Rezzo Pires; Maria do Carmo Leal; Antônio Augusto Moura da Silva (Cadernos de Saúde Pública)
Temporal trends in cesarean section (C-sections) rates were analyzed in Brazil and its regions using the Robson classification system. An ecological time-series study was conducted with data from the Brazilian Ministry of Health about C-section rates from 2014 to 2022. Joinpoint models were used to estimate percentage changes in C-section rate trends in the units of analysis. C-section rate in the study period was 56.4%. Robson groups with low expected C-section values (R1 to R4) represented 46% of the total rate of C-sections, with higher rates in the R2 and R4 groups. In these groups, rates increased significantly in Brazil and all its regions during the study period. However, a significant decrease in rates was observed in the R1 and R3 groups, from 2014 to 2016 in Brazil and in the North, Northeast, and Southeast regions. Despite its larger relative size among groups and greater contributions to the total C-section rate, the R5 group had a small but significant increase in rates in the Central-West Region only. Groups with higher expected values for C-sections (R6 to R10) showed a general upward trend, except for R9. The results indicate an excess of C-sections in Brazil and its regions, especially in low obstetric risk groups. Therefore, efforts to reduce unnecessary C-sections should be based on interventions to improve labor management in nulliparous women and promote vaginal birth after the procedure.